PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY DAN INOVASI PRODUK TERHADAP BRAND LOYALTY STARBUCKS COFFEE DI DENPASAR - Krisopras, Almez; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 5 No 4 (2016), 2016)
The marketing strategy has an important role in the survival of the company to improve customer loyalty, because marketing is the spearhead of a company. The purpose of this study was to examine and explain the effect of product innovation and Corporate Social Responsibility program product for Brand Loyalty Starbucks Coffee to customers residing in the city of Denpasar. This research was conducted at Starbucks Coffee in Denpasar, a sample of 100 respondents were taken by purposive sampling method. Collecting data by questionnaires by using a 5-point Likert scale, measuring 13 indicators. The analysis technique used is multiple linear regression analysis. These results indicate that the variable product innovation and corporate social responsibility and significant positive effect on brand loyalty in Starbucks Coffee Denpasar. These results indicate if the product innovation and corporate social responsibility of the company increases, will improve also the acceptance of Starbucks Coffee brand loyalty in Denpasar.
Keywords: brand Loyalty; corporate social responsibility; inovasi produk; strategi pemasaran.